THE USE OF FLASH CARD MEDIA TO INCREASING ARABIC VOCABULARY MASTERY (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the low mastery of Arabic vocabulary and the lack of motivation of students in learning Arabic. Because the teacher only focuses on teaching materials contained in the teacher's handbook and the lack of use of interesting learning media, especially on Arabic vocabulary material, results in low student vocabulary mastery. Based on the description above, the researcher wants to describe the process of using Flashcard media & measure its effectiveness in increasing the memorization of Arabic vocabulary at MI Miftahul Ulum, Pabuaran, Subang. This classroom action research aims to measure the effectiveness of using Flashcard media on the mastery of mufradat Arabic in class VI MI Miftahul Ulum, Pabuaran. The subjects of this study were 26 students of class VI MI Miftahul Ulum Pabuaran. This research was conducted in three cycles. Based on the results of the study, it was found that there was an increase in learning outcomes by using flashcard media. In the pre-cycle of student learning outcomes in Arabic subjects by 73%. In cycle I (first), student learning outcomes in Arabic subjects increased to 77%. In cycle II (second), student learning outcomes in Arabic subjects increased to 82%. Whereas in cycle III (third), student learning outcomes in Arabic subjects experienced a significant increase to 87%.